Development and Nutritional Evaluation of Kepok Banana Corm Flour Cookies as a Local Functional Food Product - Friedrich Andrew Saputra; Telly F.S. Tangkere; Henny N. Tambingon (Journal of Innovative and Creativity, 2025)
This study aimed to develop cookies made from kepok banana corm flour as a functional food product that supports local food diversification and the utilization of underused agricultural resources. The research sought to process banana corm into flour, formulate Good Time FAS cookies, analyze their nutritional content, and evaluate their sensory acceptability. Materials and methods included the production of banana corm flour through peeling, slicing, lime-water soaking, oven drying at controlled temperature, milling, and sieving. The cookie formulation underwent iterative refinement before being tested through laboratory-based nutritional analysis and a hedonic organoleptic evaluation involving thirteen panelists. The results showed that banana corm flour produced a fine, stable powder suitable for baking, and the formulated cookies exhibited nutritional values of 36.65% carbohydrates, 3.92% protein, 29.82% fat, and 14.50% crude fiber. These values demonstrate the flour’s capacity to enhance fiber content compared to wheat-based cookies. Sensory evaluation revealed strong consumer acceptance, with high preference ratings for texture, taste, color, and aroma, indicating that the partial substitution of wheat flour with banana corm flour did not diminish hedonic quality. The findings confirm that banana corm flour can be effectively incorporated into cookie products, contributing to the development of nutrient-rich, locally sourced snacks while providing a sustainable alternative to imported wheat flour. The study highlights the potential of banana corm as a value-added ingredient and encourages further product development and optimization.